Fa'aliyah al-Wasīlah Plotagon Story fi Ta'līm Mahārah al-Kalām min Manżur al-Manhaj al-Mustaqil: The Effectiveness of Plotagon Story in Teaching Speaking Skills from the Perspective of the Independent Curriculum to Students of Soebono Mantofani Islamic Junior High School, Tangerang - Muhamad Ihwanul Muslimin; Muhammad Fahrudin Nur; Muhammad Najib; Nur Annisa Safuroh (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2025)
The researcher chose this subject from a change in the curriculum in Indonesia from the 2013 curriculum to the independent curriculum, and of course many differences between them. The researcher found that some of the school's pupils were weak in Arabic speech, because some were afraid to make a mistake when speaking. Some pupils are vulnerable in their tendencies to learn Arabic, as some are lazy in the education process. The aim of this research is to reveal the result of the tests using the Plotagon Story method for pupils' independent curriculum and use, and to reveal the effectiveness of this method in teaching speech skill. This research followed a semi-empirical study based on the quantitative input, its design from the experimental group and control group, and its community of seventh grade pupils in the Soebono Mantofani Islamic School of 120 pupils, and appointed the researcher to 20 pupils as pilot group and 20 pupils as control group. The researcher used data collection methods as direct observation, personal interview, tests, and questionnaires. After analyzing the data, the researcher reached the averages of the tribal and postgraduate tests. Based on the average results of the pilot group on the value of 47.4 and the average results of the control group on the value of 17,05, the average results of the pilot group are greater than the average results of the control group. I came up with the analysis of the data with the test rule "v" as a result of the calculation (t0) is 9, 2 the table is at the level of 5% indication of the value of 1, 677 and the level of 1% indication of the value of 2, 407 that shows that the zero hypothesis (h0) is unacceptable and the alternative hypothesis (ha) is acceptable. This means that the use of Plotagon Story method of teaching speech skill from the perspective of the independent curriculum of the pupils of this school is statistical.